2018
DOI: 10.1080/14737167.2018.1501680
|View full text |Cite
|
Sign up to set email alerts
|

Event simulation and external validation applied in published health economic models for obesity: a systematic review

Abstract: This study aims to determine methodological variations in the event simulation approaches of published health economic decision models, in the field of obesity, and to investigate whether their predictiveness and validity were investigated via external event validation techniques, which investigate how well the model reproduces reality. Areas covered: A systematic review identified a total of 87 relevant papers, of which 72 that simulated obesity-associated events were included. Most frequently simulated event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Based on a previous systematic review identifying 87 health economic obesity models [7,8], the models for replication were selected using an expert panel consensus [9]. The panel assessed the key structural modeling approaches applied in published obesity models, and provided an expert consensus to improve the methodology and consistency of the application of decision-analytic modeling in obesity research.…”
Section: Model Selection and Model Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on a previous systematic review identifying 87 health economic obesity models [7,8], the models for replication were selected using an expert panel consensus [9]. The panel assessed the key structural modeling approaches applied in published obesity models, and provided an expert consensus to improve the methodology and consistency of the application of decision-analytic modeling in obesity research.…”
Section: Model Selection and Model Overviewmentioning
confidence: 99%
“…Consequently, complex modeling frameworks simulated over long-term horizons are required, and these carry the potential risk of errors by the modeler and/or misinterpretations by the reader. In order to investigate the reproducibility of results in this context, we have selected health economic obesity models for replication, on the basis of a previously published systematic review [7,8] and on the basis of previously published structural quality criteria for health economic obesity models [9]. The field of obesity modeling is in general very diverse; this is driven by multiple preventive and therapeutic approaches and multiple complications and comorbidities, which have triggered the development of various unique modeling approaches.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such evaluations allow decision makers to make an informed judgement on the health economic impact of an intervention, by assessing the additional benefits of funding an intervention relative to its additional costs [7]. As shown in systematic reviews [8,9] decision analytic modelling has commonly been used to evaluate the longterm economic consequences of obesity prevention and therapy measures. In the context of these obesity related decision models the key structural aspects are of fundamental influence as they are impacting all outcomes simulated by the model, including clinical parameters & events, quality of life, direct and indirect costs and hence the whole spectrum of relevant economic consequences [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was shown that there are huge variations in the structural modelling approaches focusing on the prevention and therapy of obesity [8,9] and up to now no consensus meeting on the structural aspects of obesity models has been performed. This makes it difficult for researchers to select an appropriate approach when designing a model, and subsequently for policy makers and stakeholders to assess the quality of an applied model, intended to inform political or medical decision making.…”
Section: Introductionmentioning
confidence: 99%